Clinical Presentation and Staging of Retinoblastoma Patients - Shrestha, Jyoti Baba (Journal of Institute of Medicine Nepal, 2024)
Introduction Retinoblastoma is the common curable primary intraocular malignancies of childhood occurring in approximately 1 in 18,000 live births. The burden of disease is of great importance because early detection and management will have a lifelong impact on other domains of development in these children. The purpose of this study is to determine the clinical presentation and staging of retinoblastoma patients. Methods This was a hospital-based descriptive study conducted at BP Koirala Lions Centre for Ophthalmic Studies. Children diagnosed with retinoblastoma were enrolled by purposive sampling method. After obtaining informed written consent, data was taken in semi-structured proforma. Data was analysed in the SPSS version 21.0. Results A total of 17 cases of retinoblastoma were enrolled in this study. Majority of the cases were male, belonging to low-class family, and from rural areas. Sixty four percent of participants had leukocoria, followed by proptosis (18%) and red eye (9%). One eye was affected in 12 (71%) cases and both eyes were affected in 5 (29%) cases. The highest number of patients was from Province 2 (35%) and they belonged to the upper caste (29%). Group D and group E lesions were seen in 37% and 50% of cases respectively whereas stage 1 disease was seen in 86%. Conclusion Leukocoria was the most common clinical presentation. More than 80% of tumours were in advanced Group D and Group E category. The study highlights the delayed presentation of cases to treatment because of lack of awareness, ignorance, poverty, illiteracy and limited access to health care facilities.